Effects of Foreign Aid in SADC Region: A Case for Malawi - Chalamba, Leah (Graduate School of Business (GSB), 2022)
Most underdeveloped countries continue to receive Official Development Aid, and Malawi is not an exception. This research paper examined the effect of Official Development Aid on the Gross Domestic Product and Human Development Index in Malawi, using annual time series data from 1990 to 2018. In addition, the relationship of Gross Domestic Product, Human Development Index and Official Development Aid was analysed using cointegration, correlation and granger causality techniques. The results of cointegration indicated a short term relationship among the variables, hence the Vector Autoregressive (VAR) Model was used together with Ordinary Least Squares (OLS) to study the effect of Official Development Aid to Human Development Index and the effect of Official Development Aid to Gross Domestic Product. In the first VAR Model Equation, Gross Domestic Product was significantly positively influenced by Trade Openness and lagged value of Gross Domestic Product. In the second VAR Model Equation, Official Development Aid and lagged value of Human Development Index were found to positively influence Human Development Index from 1990 to 2018. In addition, Official Development Aid showed significant influence to GDP. In summary, Official Development Aid showed significant positive influence to Human Development Index, while indicating varied results regarding influence to Gross Domestic Product. Findings suggest that policy makers in Malawi should gradually stop relying on donors, explore targeted foreign aid and think of other innovative ways like changing policies on trade openness and human development to boost the country's GDP, among others.